Penggunaan Teknik 5 Jari Untuk Mengatasi Kecemasan Di SMA Al-Azhar - Rahma Elliya; Muhammad Rafli; Ilham Agung Sakti; Anggun Istawala; Endah Fajrianti; Mahda Rizka F.R; Niluh Sumo (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Anxiety is related to fear and manifests as a mood state. Anxiety can be caused by several factors such as biological factors and psychosocial factors. anxiety can affect mood, cognitive, motor activity. Adolescence is a transition period from childhood to adulthood. In this phase, adolescents experience several major changes such as growth in body size, physical abilities, and physiological changes. Emotional turmoil, which occurs rapidly in early adolescence is known as a period of storm and stress. One therapy to reduce anxiety is 5 finger therapy. in this study, counseling was conducted on the use of the 5 finger technique to overcome anxiety at AL-AZHAR High School. this therapy method is carried out for ± 10 minutes with concentration and relaxation. this method causes a relaxation effect so that it reduces tension, stress and anxiety.